Islam and Crucial Issues in the Political Communication of the Indonesian Solidarity Party - Nopriyansa, Eko (Jurnal Politik Indonesia: Indonesian Political Science Review, 2021)
Lately, Indonesia, such as corruption, intolerance, radicalism, terrorism, and various social problems, can be a complex case; social anxiety in Indonesia recently needs a solution that can solve problems without specific religious schemes. The presence of the Partai Solidaritas Indonesia, chaired by Grace Natalie recently and is known as a young Christian female political figure amid the world's largest Muslim majority population, political battles in various attempts to gain public support is the biggest challenge for the Partai Solodaritas Indonesia. Several steps of the PSI have attracted debate. Several Muslim groups have criticized them for being considered to be making crucial narratives by not considering Indonesia existing religious values in political narratives, such as the unconditional rejection of Sharia Law, rejecting polygamy as a social problem, thus inviting debate and getting severe reactions for some Indonesian Muslim groups. This paper attempts to thoroughly dissect the various paradigms and narratives of the Indonesian Solidarity Party in political communication, analyze the principles of the concept of the State, and examine the Islamic concept in-depth, comprehensively and can answer the recent socio-political discourse.